ANALISIS DEIKSIS PERCAKAPAN MAHASISWA DI UNIVERSITAS MUHAMMADIYAH TANGERANG PADA PENDIDIKAN BAHASA INDONESIA - Riska Oktaviani; Intan Sari Ramdhani (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
The purpose of this research is to define some deixis and examine how Indonesian students interact. The methodology used in this research is descriptive. The conversation of Indonesian language education students is described in this study using data deixis, which includes persona deixis, place deixis, time deixis, discourse deixis, and social deixis. The primary data source for this research comes from conversations among students of Indonesian language education in both formal and informal contexts. National lectures, conversations with other students, and casual conversations are examples of informal activities. Discussions between students and lecturers are formal activities (in canteens, boarding houses, rice stalls, etc.). Data collection techniques involving recording and wiretapping. Research data analysis was carried out using a descriptive approach. Persona deixis (plural first person singular) is one of the conclusions of the study.